2018
DOI: 10.1002/mdc3.12687
|View full text |Cite
|
Sign up to set email alerts
|

22q11.2 Deletion Syndrome–Associated Parkinson's Disease

Abstract: Background22q11.2 deletion syndrome (22q11.2DS) is a multisystem condition associated with an increased risk of early‐onset Parkinson's disease (PD).MethodsWe review the clinical, neuroimaging, and neuropathological observations, as well as diagnostic challenges, of PD in 22q11.2DS. We conducted a search of PubMed up until June 1, 2018 and personal files to identify relevant publications.Results22q11.2DS‐associated PD is responsible for approximately 0.5% of early‐onset PD. The hallmark motor symptoms and neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 52 publications
0
27
0
2
Order By: Relevance
“…Psychotic symptoms sometimes improved with clozapine, quetiapine, and valproic acid . Special attention should be paid to the risk of clozapine‐associated seizures …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychotic symptoms sometimes improved with clozapine, quetiapine, and valproic acid . Special attention should be paid to the risk of clozapine‐associated seizures …”
Section: Resultsmentioning
confidence: 99%
“…This multisystem condition is associated with an increased risk of early-onset PD. 38 The prevalence of psychosis in this condition ranged between 10% and 30% and developed usually during childhood or early adulthood. [39][40][41] Psychotic symptoms included auditory and visual hallucinations, as well as paranoid delusions.…”
Section: Q112 Deletion Syndromementioning
confidence: 99%
“…While PARK2 is a bona fide PD gene, deletions of chromosome 22q11.2 (22q11.2DS, OMIM # 188400) have only recently been implicated in PD [97,98]. The 22q11.2 deletion is considered to be one of the most common deletion syndromes (~1:1,000-3,000 births) and was first described in 1968 [99,100].…”
Section: Q112 Deletion/di George Syndrome Linked To Parkinsonismmentioning
confidence: 99%
“…I read with great interest the recent review article by Boot et al on Parkinson's disease in 22q11 deletion syndrome . There is evidence to suggest an increased risk of Parkinson's disease among people with 22q11 deletion syndrome.…”
mentioning
confidence: 99%
“…Dear Sir, I read with great interest the recent review article by Boot et al on Parkinson's disease in 22q11 deletion syndrome. 1 There is evidence to suggest an increased risk of Parkinson's disease among people with 22q11 deletion syndrome. In our study of 50 adults with 22q11 deletion syndrome, we identified an increased prevalence of potential clinical markers of prodromal neurodegeneration (e.g., hyposmia).…”
mentioning
confidence: 99%